Hubungan antara Pendidikan Ibu dengan Kemampuan Mean Leaghth of Uterance (MLU) pada Anak Usia Prasekolah di Raudhatul Athfal AL Kautsar Surakarta - Luthfiyyah, Adillah; Setyaningsih, Wiwik; Ekasari, Tetty (Jurnal Terapi Wicara dan Bahasa, 2023)
Abstract Background: Mother's education is one of the factors that influence the average number of child morpheme utterances. The results of the 2018 Riskesdas, that the percentage of children's language problems is 0.42%. Objectives:To find out the description of the education level of mothers with preschool-aged children, o find out the MLU of preschool age children. (3) To determine the relationship between mother's education and Mean Length of Uterance (MLU) skills in preschool-aged children in RA Al Kautsar Surakarta. Methods: This research is a quantitative study using a purposive sampling technique, the sample in this study were 30 children who attended school at RA Al Kautsar Surakarta. The statistical test used in this study is the Chi Square test. Results: Based on the results of the chi-square test, a significance value of 0.000 was obtained, which means p <0.05, so there is a relationship between maternal education and MLU abilities in preschool-aged children at RA Al Kautsar Surakarta. Conclusion: The results of the Chi Square test analysis show that Ha is accepted, which means that there is a significant relationship between mother's education and MLU abilities in preschool-aged children at RA Al Kautsar Surakarta. Keywords: MLU, Maternal education, Preschool age children